Monitoring the Future: A Continuing Study of American Youth, 2020 (Restricted-Use) - Miech, Richard A. ([Verlag nicht ermittelbar], 2021)
This data collection is part of the Monitoring the Future series that explores changes in important values, behaviors, and lifestyle orientations of contemporary American youth in eighth, tenth, and twelfth grades. The restricted data sets in this collection include variables that were altered or omitted from the public use data sets to maintain respondent confidentiality. Examples of variables included in their original form are: unaltered sampling weight variable, variables for strata and cluster to account for the complex sample design of the MTF, and previously-omitted data on some variables for the Western region of the US. For each year from 1976 through 2017, two data sets containing data for all three grades are available: one dataset including school-level state, county, and Zip Code variables, and one dataset without these geographic school-level variables. Beginning with 2018, data sets were created separately for 8th/10th and 12th grades, resulting in four data sets. This split on grade was done to mirror the data availability of the public use files and facilitate the merging of the public and restricted use data. Please note: Use of the geographic identifiers such as state, county, or zip code is limited and researchers interested in these variables are encouraged to read FAQs: Monitoring the Future Restricted-Use Geographic Variables Also included as part of each annual collection is a zip archive of the Monitoring the Future public-use data and documentation for each respective year. The basic research design used by the Monitoring the Future study involves annual data collections from eighth, tenth, and twelfth graders throughout the coterminous United States during the spring of each year. The 8th/10th grade surveys consist of four different questionnaire forms (only two forms from 1991-1996) and the 12th grade surveys consist of six questionnaire forms (only five forms from 1976-1988). Identical forms are used for both eighth and tenth grades, and for the most part, questionnaire content is drawn from the twelfth-grade questionnaires. Thus, key demographic variables and measures of drug use and related attitudes and beliefs are generally identical for all three grades. However, many fewer questions about lifestyles and values are included in the 8th/10th grade surveys. Drugs covered by these surveys include tobacco, smokeless tobacco, alcohol, marijuana, hashish, prescription medications, over-the-counter medications, inhalants, steroids, LSD, hallucinogens, amphetamines (stimulants), Ritalin (methylphenidate), sedatives/barbiturates tranquilizers, cocaine, crack cocaine, ecstasy, methamphetamine, heroin, and GHB (gamma hydroxy butyrate). Other topics include: attitudes toward religion, changing roles for women, educational aspirations, self-esteem, exposure to drug education, and violence and crime (both in and out of school).